Catecholaminergic innervation and D2-like dopamine receptor-mediated modulation of brainstem nucleus incertus neurons in the rat. (1st November 2022) - Szlaga, Agata; Sambak, Patryk; Gugula, Anna; Trenk, Aleksandra; Gundlach, Andrew L.; Blasiak, Anna
Abstract: Nucleus incertus (NI) is a brainstem structure involved in the control of arousal, stress responses and locomotor activity. It was reported recently that NI neurons express the dopamine type 2 (D2) receptor that belongs to the D2-like receptor (D2R) family, and that D2R activation in the NI decreased locomotor activity. In this study, using multiplex in situ hybridization, we observed that GABAergic and glutamatergic NI neurons express D2 receptor mRNA, and that D2 receptor mRNA-positive neurons belong to partially overlapping relaxin-3- and cholecystokinin-positive NI neuronal populations. Our immunohistochemical and viral-based retrograde tract-tracing studies revealed a dense innervation of the NI area by fibers containing the catecholaminergic biosynthesis enzymes, tyrosine hydroxylase (TH) and dopamine β-hydroxylase (DBH), and indicated the major sources of the catecholaminergic innervation of the NI as the Darkschewitsch, raphe and hypothalamic A13 nuclei. Furthermore, using whole-cell patch clamp recordings, we demonstrated that D2R activation by quinpirole produced excitatory and inhibitory influences on neuronal activity in the NI, and that both effects were postsynaptic in nature. Moreover, the observed effects were cell-type specific, as type I NI neurons were either excited or inhibited, whereas type II NI neurons were mainly excited by D2R activation. Our results reveal that rat NI receives a strong catecholaminergic innervation and suggest that catecholamines acting within the NI are involved in the control of diverse processes, including locomotor activity, social interaction and nociceptive signaling. Our data also strengthen the hypothesis that the NI acts as a hub integrating arousal-related neuronal information. Graphical abstract: Image 1 Highlights: NI neurons expressing D2 mRNA can express both vGAT and vGlut mRNA. D2 mRNA is expressed in relaxin-3- and cholecystokinin-positive NI neurons. Main sources of NI catecholamines are the Darkschewitsch, raphe and A13 nuclei. Type I NI neurons can be excited or inhibited by D2R activation. Type II NI neurons are mainly excited by D2R activation.